Realisasi Anggaran Pendapatan dan Belanja Daerah (APBD) Provinsi Sumatera Utara pada Tahun 2020 (Indo-MathEdu Intellectuals Journal, 2023)
The purpose of this study is to determine and analyze the level of effectiveness and efficiency of regional budgets. The type of research used is qualitative descriptive research. The research data for the 2020 period uses secondary data in the form of Budget Realization Reports obtained from the website of the Central Statistics Agency (BPS) of North Sumatra Province and also data obtained through literature studies and the internet conducted by collecting and studying literature. which is a book. The results of this study show that the Regional Budget is the annual financial plan of the government in Indonesia approved by the House of Representatives. The Regional Revenue and Expenditure Budget is determined by local regulations. The Regional Revenue and Expenditure fiscal year covers a period of one year.